PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SBS ( SARI BUAH SAWIT ) KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Eria, Elsa; Sari, SE.MM, Mareta Kemala; Amaluis,SE.MM, Dina (Pendidikan Ekonomi, 2014)
ABSTRACT Elsa Eria (09090258) , Influence of Leadership Style Of Employee Satisfaction On PT SBS. Fruit Oil , district. Kinali , Kab . Pasaman West . Thesis , Economic Studies Program , STIKP PGRI West Sumatra , Padang , 2014 under the guidance of Mrs. Mareta Kemala Sari , SE.MM and Dina Amaluis , SE , MM .This research was motivated by the lack of compensation on PT . SBS . Fruit Oil , District Kinali West Pasaman caused to lack of job satisfaction . This study aims to determine whether there is influence of leadership style on job satisfaction of employees of PT . SBS ( Palm Fruit Extract ) Kinali District of West Pasaman .This research is a descriptive study associative . The population in this study were all employees PT.SBS ( Palm Fruit Extract ) Kinali District of West Pasaman . The study sample was an employee of PT . SBS ( Palm Fruit Extract ) accounted for 92 employees who serve as population , sample collection technique research instrument used was a questionnaire . To determine the effect of leadership style on employee job satisfaction is used by t test analysis techniques .Based on testing hypotheses derived tcount 8.603 > 1.661 ttabel value , meaning that Ho refused and H1 accepted . It can be concluded leadership style affects job satisfaction PT.SBS ( Palm Fruit Extract ) Kinali District of West Pasaman . The magnitude of the effect of leadership style on employee job satisfaction Based on the findings , the researchers suggest for the leadership and for further research , namely the need to improve job satisfaction while the remaining 45.1 % 34.9 % influenced by factors beyond 0leh from the education . Based on the research results , the researchers suggest for the employees always keep in working condition until the leaders were satisfied , one of which the employee is expected to work for always taking into account the work . For researchers selanjunya order also to examine other variables outside variables by researchers in order imflikasinya greater .